If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(2x + 5) = -27 Reorder the terms: -3(5 + 2x) = -27 (5 * -3 + 2x * -3) = -27 (-15 + -6x) = -27 Solving -15 + -6x = -27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + -6x = -27 + 15 Combine like terms: -15 + 15 = 0 0 + -6x = -27 + 15 -6x = -27 + 15 Combine like terms: -27 + 15 = -12 -6x = -12 Divide each side by '-6'. x = 2 Simplifying x = 2
| 17-6xn=47+10xn | | 5*5=-45 | | 4x-6x+14x-21=0 | | 8-(5/x)=9-(10/x) | | d(3+c)= | | 69+p=96 | | 9x^2-90x+223=0 | | 12=4a | | 2x^2-9y+10=0 | | 3x+2x-17=8 | | 2=45pr | | 4x1/2 | | 24=-x-7x | | t-[-16]=9 | | 12-5r=-48 | | 7x-3=8x-4 | | x^2-x^2-2x-2x+4=40 | | -5=-6-3x+s+1 | | -11=k+[-5] | | -3(8x+11)=6(-4x-(13)) | | 7=(10-g)/-2 | | 5m-12=27 | | (x-4)*y=200 | | 3x^2-41+110=0 | | 10x-60= | | (2+5i)+(-1+5i)= | | b/12-100=25 | | x/-3=11 | | 6x-1=5x-6 | | 9t-10=17-9t | | 5+w/8=30 | | 4r+5s-16r+3s= |